The Story About the Witch of Endor in the Writings of the Early Church Fathers - Gjorgjevski, Gjoko; Todorovska, Marija (ВТУ „Св. св. Кирил и Методий“, София, 2016)
The story of the witch of Endor (1 Samuel 28, 3–25) and the events surrounding it have generated great interest for readers starting from the early church history. According to the story, Saul, the first king of Israel, visited the sorceress (despite the ban of all witchcraft throughout the kingdom) and asked her to conjure up the spirit of the prophet Samuel, so he could tell his fortune. The necromancer evoked the spirit identified by Saul as Samuel, who informed Saul that he and his three sons would die in combat the next day during the battle with the Philistines. This episode from the II century has been the subject of many varied interpretations, which can be separated into three main groups of opinions on the status of the witch/necromancer: 1) the woman of Endor did, actually, have the power to call Samuel back from Sheol; 2) the evocation was a result of a deception by the devil who was, in fact, the one to appear to Saul; and 3) Samuel actually appeared to Saul, but not because of the power of the necromancer, but because of the will of God. From the broad exegetical material on the issue, a compilation which includes interpretations of Origen, of Eustathius and of Gregory of Nyssa is presented, as a result of the work of an unknown Byzantine scholar who gathered together these three texts (attested by the codex Monacensis Graecus 331 of X century). The present text does not grant a definite answer to the ontological and dogmatic status of the witch of Endor, but offers brief overviews of the stances of Origen, Eusthatius and Gregory of Nissa, showing the richness of interpretation and research of the story and its implications.